Archimedes - Keating, Susan Katz.; Tartarotti, Stefano, 1968- (Philadelphia : Mason Crest Publishers, 2003)
Recalls stories about the life and work of the famous Greek mathematician, Archimedes, using accounts from the writings of a contemporary Roman statesman, Cicero.
Keywords: Archimedes -- Juvenile literature; Archimedes; Mathematicians -- Greece -- Biography -- Juvenile literature; Mathematicians